The Role of the Inhibitory Ligand HVEM and Its Receptors CD160 and BTLA in the Regulation of Anti-retroviral T Cell Responses - David, Paul; Westmeier, Jaana; Drabczyk-Pluta, Malgorzata; Werner, Tanja; Ickler, Julia; Francois, Sandra; Bayer, Wibke; Sutter, Kathrin; Del Rio, Maria Luisa; Rodriguez-Barbosa, Jose-Ignacio; Dittmer, Ulf; Zelinskyy, Gennadiy (Frontiers in Virology, 2022)
Specific CD8+ T cells are crucial for the control of viruses. However, during many chronic viral infections these cells become dysfunctional. Immune checkpoint receptors, like PD-1 expressed on CD8+ T cells, contribute to this functional suppression during chronic infection. However, during the acute phase of infection virus-specific CD8+ T cells express high levels of PD-1 but are fully competent in killing virus-infected cells and there is increasing evidence that the biological activity of inhibitory receptors is strongly influenced by the availability of their respective ligands. We determined the expression of ligands for inhibitory receptors on infected myeloid cells during the acute phase of Friend retroviral (FV) infection. FV infection of granulocytes, monocytes, and macrophages strongly increased the cell surface expression of PD-L1 and the recently described ligand HVEM for inhibitory receptors BTLA and CD160. In addition, the infection of human myeloid cells in vitro with HIV also enhanced the expression of PD-L1 and HVEM. In infected mice, the up-regulation of inhibitory ligands on infected cells was accompanied by enhanced frequencies of FV-specific CD8+ T cells that express PD-1, and the inhibitory receptors CD160 and BTLA. To define the functional effects of HVEM on activated CD8+ T cells, FV-infected mice were treated with blocking antibodies that prevented the interaction of HVEM with its two receptors, CD160 or BTLA, alone or in combination with anti-PD-L1 antibodies. Blocking the interaction of HVEM with CD160 and BTLA improved the production of cytotoxic molecules and the elimination of FV-infected cells. This effect was augmented when the therapy was combined with anti-PD-L1 antibodies, resulting in an additional expansion of cytotoxic CD8+ T cells. Thus, the ligand HVEM for the inhibitory receptors CD160 and BTLA downregulates the functionality of CD8+ T cells during retroviral infection and are potential targets for the immunomodulatory therapy of chronic viral infections.